Pig Management Strategies in the East Liao River Basin From the Bronze Age (c. 2000–256 BC) to the Liaojin Dynasties (907–1234 AD): Stable Isotope Analysis of Animals at the Changshan Site, Jilin Province, China - Lv, Xiaohong; Ban, Lin; Liu, Yiwen; Guan, Ying; Liu, Hailin; Wang, Chunxue; Hou, Liangliang (Frontiers in Earth Science, 2022)
Pig domestication and management strategy has been increasingly discussed in recent years, focusing on the temporal-spatial differences of pig management strategies. The East Liao River Basin with diverse ecosystems, cultural exchanges, and collisions plays an important role in the cultural development, exchange, and integration processes between Northeast China and the Central Plains. Multiple studies have revealed that various forms of subsistence economy, such as nomadism, fishing and hunting, and farming, existed in this region. However, no report or discussion has been presented concerning the status of domestic animal management strategies over a long-term in the East Liao River Basin. Carbon and nitrogen stable isotopes analysis were performed on the fauna bones at the Changshan site in Siping, Jilin, China, from the Bronze Age (c. 2000~256 BC) to the Liaojin Dynasties (907~1234 AD), to reconstruct their dietary pattern and reveal the status of domestic animal management strategies, especially the diachronic changes in pig feeding strategies. The results showed that pigs (–19.3±1.6‰, 5.3±0.9‰, n=27), horses (–18.4±1.7‰, 4.8±1.4‰, n=7), and sheep (–19.8±1.5‰, 5.7±0.5‰, n=6) primarily received their subsistence through C3-based food. Nevertheless, cattle (–16.4±3.5‰, 6.0±2.1‰, n=2) and the past human (–13.9‰, 10.3‰, n=1) lived on mixed C3/C4-based food. Notably, the stable isotope data for pigs from the Bronze Age (–19.1±2.0‰, 5.4±1.0‰, n=9) to the Liaojin Dynasties (–19.8±0.6‰, 5.1±0.7‰, n=15) were similar, indicating that the management and/or feeding strategy of domestic pigs were relatively stable with a free range in a wild ecosystem over a long period. Related studies have shown that pigs in captivity were mainly fed by millet-based food in the West Liao River Basin and the middle reaches of the Yellow River valley, where millet agriculture were adequately developed. Abundant natural resources, including plants, wild animals, and fishes, could provide sufficient food to the human population in the East Liao River Basin. Thus, the millet-based agriculture was just an auxiliary subsistence strategy in the Changshan site, leading to a gap in the driving force for long-term intensive management of pig.